Pathogenicity and transcriptome analysis of a strain of Vibrio owensii in Fenneropenaeus merguiensis. Issue 130 (November 2022) - Dai, Linxin; Xiong, Zhiwang; Hou, Danqing; Wang, Yue; Li, Ting; Long, Xinxin; Chen, Haozhen; Sun, Chengbo
Abstract: Vibrio is an important conditional pathogen in shrimp aquaculture. This research reported a dominant bacteria strain E1 isolated from a shrimp tank with the method of biofloc culture, which was further identified as Vibrio owensii . To understand the interaction between V. owensii and the host shrimp, we studied the pathogenicity of the V. owensii and the molecular mechanisms of the Fenneropenaeus merguiensis immunity during the Vibrio invasion. Drug susceptibility tests showed that V. owensii was resistant to antibiotics streptomycin oxacillin, tetracycline, minocycline, and aztreonam, but highly sensitive to cefazolin, cefotaxime, and ciprofloxacin, and moderately sensitive to cefotaxime, ampicillin, and piperacillin. Lethal concentration 50 (LC50 ) test was performed to evaluate the toxicity of V. owensii to F. merguiensis . The LC50 of V. owensii infected F. merguiensis after 24, 48, 72, 96, 120, 144 and 168 h were 1.21 × 10 7, 1.68 × 10 6, 6.36 × 10 5, 2.15 × 10 5, 7.58 × 10 4, 5.55 × 10 4 and 4.33 × 10 4 CFU/mL. In order to explore the molecular response mechanism of F. merguiensis infected with V. owensii, the hepatopancreas of F. merguiensis were sequenced at 24 hpi and 48 hpi, and a total 40, 181 of unigenes were obtained. Through comparative transcriptomic analysis, 86 differentially expressed genes (DEGs) (including 38 up-regulated DEGs, and 48 down-regulated DEGs) and 305 DEGs (including 150 up-regulated DEGs, and 155 down-regulated DEGs) were identified at 24 hpi and 48 hpi, respectively. Annotation and classification analysis of these 391 DEGs showed that most of the DEGs were annotated to metableolic and immune pathways, which indicated that F. merguiensis responded to the invasion through the regulation of material metableolism and immune system genes during V. owensii infection. In the KEGG enrichment analysis, some pathways related to immune response were significantly influenced by V. owensii infection, including phagosome, MAPK signalling pathway and PI3K-Akt signalling pathway. In addition, some pathways related to the warburg effect were also significantly enriched after V. owensii infection, including pyruvate metableolism, glycolysis/gluconeogenesis, and citrate cycle (TAC cycle). Further analysis showed that C-type lectins and ficolin were also play important roles in the immune response of F. merguiensis against V. owensii infection. The current research preliminarily revealed the immune response of F. merguiensis to V. owensii infection at the molecular level, which provided valuable information to further understand the disease control and the interaction between shrimp and Vibrio . Highlights: Established Vibrio owensii infection model. Measured drug resistance and virulence of V . owensii. The first hepatopancreas transcriptome profile of V . owensii infection in the shrimp, F . merguiensis, was constructed. Warburg effect may also occur during V . owensii infection in F . merguiensis.